Proses Komunikasi Pemerintah Daerah Istimewa Yogyakarta dalam Menyalurkan Jaminan Sosial Lanjut Usia - Nur Izzaturrahmah; Dian Eka Rahmawati (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
The increase in the number of elderly people in Indonesia, especially in the Special Region of Yogyakarta (DIY), will reach 16.69% by 2023. This creates new challenges in fulfilling the social and economic rights of this vulnerable group. The DIY government responded through the Social Security for the Elderly (JSLU) program to ensure the welfare of the poor and neglected elderly. This research uses a qualitative approach with secondary data obtained from official government websites, digital mass media, and scientific articles. The analysis was conducted based on Harold Lasswell's communication process theory, which includes five indicators: who (communicator), says what (message), to whom (communicant), through what channel (media), and with what effect (resulting impact). The results showed that the DIY government's communication in distributing JSLU was quite effective. The local government, Department of Social Affairs, and partners such as Bank BPD DIY and warung WALUYO act as credible communicators. Messages are delivered clearly through socialization and digital media. Communicants (the elderly) receive information through various media, although some face barriers in accessing technology. The effectiveness of communication can be seen from the achievement of aid distribution of 97.76% of the target of 8,000 elderly. The JSLU program not only improves the welfare of the elderly but also empowers the local economy through neighborhood stalls. However, challenges such as limited access to technology for the elderly and the lack of socio-economic impact evaluation need to be addressed. The success of the program depends on the continuity of inclusive communication and continuous monitoring.